171 Developing & Centralising a Nurse-Led Local Anaesthetic (La) Transperineal (Tp) Biopsy Service During Covid: A Success Story. (28th February 2022) - Winters, D.; Mehmi, A.; Odedra, A.; Buttleman, S.; Ancheta, J.; Allchorne, P.; Rajan, P.; Khan, S.; Green, J.S.A.
Abstract: Introduction: During the first COVID-19 wave, the BAUS Section of Oncology issued guidance to minimise risks of sepsis and general anaesthesia at prostate biopsy. Consequently, and as a result of diminished diagnostics capacity on Trust acute sites, we implemented a centralised network-wide nurse-led LA TP biopsy service on a COVID-secure "green" site and abandoned trans-rectal biopsies. We evaluated the impact of this service improvement on patient waiting times before and after national lockdown in March 2020. Method: Classic Quality Improvement (QI) methodology was used with continuous data collection and waiting list management by clinical staff with standard admin support. Balancing measurements were collected. Run charts were used to confirm whether a change led to a real and sustainable improvement. Results: The number of days waiting, from time of request to date of biopsy, is presented in the following run chart. The mean waiting time for those pre lockdown was 145 days (SD 57) whereas post lockdown was 23 days (SD 20). This identified that there was a significant difference between the average waiting time pre and post lockdown (U = 55.5, p = <0.001) There were also reductions in waiting time when subcategorised into planned Active Surveillance cases, target cases and delayed cases. Conclusions: Centralising the TP biopsy service and converting to a nurse led LA service has led to reductions in waiting lists and was safely expedited and resilient even in the COVID-19 pandemic. Allowing a second advanced TP practitioner to be fully trained, during COVID. The service was highly valued by patients and staff.